COST EFFECTIVENESS ANALYSIS OF THE USE OF ANTIBIOTICS CEFTRIAXONE AND LEVOFLOXACIN IN BPJS PATIENTS URINARY TRACT INFECTION (UTI) HOSPITALIZATION AT RSM AHMAD DAHLAN KEDIRI CITY YEAR 2022 - Walujo, Djembor; Anarki, Ferrentia (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2025)
Numerous health interventions with varying degrees of success are evaluated using cost-effectiveness analysis in pharmacoeconomic research. When bacteria and other infectious microbes make their way up the urinary canal from the urethra and multiply in the bladder, it may lead to infections in the kidneys and ureters. It is estimated that gram-negative bacteria, especially Escherichia coli, are responsible for almost 90% of UTIs. Anyone, from youth to the elderly, is susceptible to urinary tract infections, which disproportionately affect females. We want to learn more about the relative merits of ceftriaxone and levofloxacin in treating UTIs at Ahmad Dahlan Hospital by conducting this cost-effectiveness analysis. In this study, we used a descriptive technique and gathered data retrospectively. To determine the cost-effectiveness, we averaged the direct medical costs and compared the ACER and ICER values. At Ahmad Dahlan Hospital in Kediri City, the average direct medical expenditure for ceftriaxone medication for UTI patients was 3,150,180 Rp. in 2022. At the same time, the same group of patients at the same hospital had average direct medical expenditures of Rp. 2,901,338 for levofloxacin antibiotics. With an ACER value of Rp. 120,889,083, levofloxacin antibiotics are determined to be the most cost-effective..